Investigation of laboratory confirmed Dengue outbreak in North-eastern Kenya, 2011 - Obonyo, Mark; Fidhow, Ahmed; Ofula, Victor (PLOS ONE, 2018)
The first laboratory confirmed dengue outbreak in Kenya was reported in coastal towns of Malindi and Kilifi in 1982. Since then, no other outbreak had been confirmed in Kenya. Dengue outbreak was confirmed among African Mission soldiers in Somalia (AMISOM) between May to October 2011. From September 2011, an upsurge of febrile patients who were negative for malaria on microscopy were reported in several health facilities in Mandera town, an adjacent area to Somalia in northern Kenya. We investigated a suspected dengue outbreak in Mandera town from 26th September 2011 to 5th October 2011. A suspected case was defined as acute onset of fever with two or more of the following: headache, arthralgia, myalgia, rash and hemorrhages and negative malaria microscopy results in a person presenting to a health facility in Mandera town from 1st August to 2nd October 2011. We prospectively identified new cases meeting the suspect case definition from 2nd October to 5th October 2011 and we collected blood samples from consenting patients. Blood was collected into plastic vacutainers and stored in dry shipper at -80oc to laboratory for dengue virus testing using real time reverse transcriptase polymerase chain reaction (rRT-PCR). We administered a standardized form to obtain clinical information. We calculated descriptive statistics to describe the outbreak. A total of 1,332 patients had been line listed by the district surveillance team, of which 381 (29%) met our suspect case definition of dengue. Cases peaked between 10th September and 1st October 2011 and thereafter declined. We prospectively identified 33 cases meeting the suspect case definition, of whom 30 (91%) were positive for dengue virus serotype 3 by PCR. Among the 30 laboratory confirmed patients, 20 (67%) required hospitalization (Median hospitalization period, two days with a range: 1–4 days)). And of these, 26 (86%) patients reported aches and pain, 16 (53%) reported vomiting, and four (13%) gingival bleeding. Twenty-three (77%) received anti-malarial therapy. Among laboratory-confirmed dengue patients, seven (23%) had malaria co-infection. This was the second confirmed Dengue outbreak in Kenya, and highlighted the need for improved surveillance to better define disease burden and continuous education to medical personnel to improve detection and clinical management. We also recommended enhanced community education for disease prevention.